Associations between personal exposures to VOCs and alterations in cardiovascular physiology: Detroit Exposure and Aerosol Research Study (DEARS). (March 2015) - Shin, Hwashin Hyun; Jones, Paul; Brook, Robert; Bard, Rob; Oliver, Karen; Williams, Ron
Abstract: Background: An adult cohort consisting of 63 participants engaged in the US EPA's recent Detroit Exposure and Aerosol Research Study (DEARS) and a University of Michigan cardiovascular sub-study conducted during summer and winter periods over 3 years between 2004 and 2007 (5 seasons in total). Through all participants' wearing of a monitoring vest, personal exposures to various air pollutants were measured. Purpose: The study objective was to identify the association between personal exposure to volatile organic compounds (VOCs) and six cardiovascular health endpoints in an adult non-smoking cohort of the DEARS. Methods: Twenty five VOCs were collected using the DEARS exposure vest incorporating advanced passive diffusion tube. Six cardiovascular health endpoints including systolic and diastolic blood pressure (SBP, DBP), heart rate (HR), brachial artery diameter (BAD), brachial artery flow-mediated dilatation (FMD) and nitroglycerin-mediated arterial dilatation (NMD) were collected by novel, in-home clinical examinations. To reduce the number of personal VOCs highly correlated to each other, a principal component analysis was conducted. Accounting for more individual variations in association between personal VOCs and cardiovascular health endpoints, a linear mixed model was employed, where cohort subjects were not necessarily to have the same linear association. Results: Applying the principal component analysis, 3 out of 12 components were retained, which appeared to involve a petroleum source (1st component), a 1-3 butadiene source (2nd component), and an ambient (Freon) source (3rd component). Petroleum related VOCs were associated with increases in FMD and showed mixed relationships with NMD (lag 0–1 day increased NMD, lag 2 days decreased NMD). Butadiene related VOCs decreased DBP but increased HR and BAD. Freon (ambient background) related VOCs increased HR. Conclusions: We observed mixed and variable results in this first study to evaluate the relationships between personal exposures to VOCs of different origin on cardiovascular physiology. In sum, the findings suggest that VOCs may have rapid impacts upon the human cardiovascular system; however, understanding the health implications and the mechanisms responsible is beyond the scope of this investigation. Highlights: VOC personal exposure monitoring was conducted in an adult cohort. Potential source categories were linked to the subsequent exposure profiles. Three primary sources were linked to the exposure profiles. Select cardiovascular changes associated with exposure profiles were observed.